FAMILY RESILIENCE IN DEVELOPMENT COMMUNICATION IN INDONESIA: A CRITICAL SYNTHESIS OF FAMILY RESILIENCE FRAMEWORK AND COMMUNICATIVE RESILIENCE - Mike Indarsih; Sarwititi Sarwoprasodjo (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Family resilience is a strategic issue in agricultural and rural development in Indonesia, particularly amidst economic vulnerability, livelihood uncertainty, and limited access to resources. The family serves as the basic social unit that supports the sustainable well-being and adaptation of rural communities. However, development communication studies still show theoretical fragmentation and minimal attention to communication as a core mechanism of resilience. This paper aims to critically review the Family Resilience Framework (Walsh) and Communicative Resilience (Buzzanell), and compare them with Sensemaking Theory (Weick), to assess their relevance and limitations in the Indonesian development context. The review was conducted through a systematic narrative approach to Scopus-indexed journal articles that empirically apply resilience theory. The results of the study indicate that Walsh's theory effectively explains the internal adaptive capacity of families, while Buzzanell emphasizes communication as a process of negotiating meaning and identity in crisis situations. However, both theories remain inadequate in explaining power relations, structural barriers, and the institutional context of rural development. This paper offers a theoretical synthesis that integrates systemic, communicative, and sensemaking approaches to understand family resilience contextually. The research implications emphasize the importance of empirical studies based in rural communities and the design of culturally sensitive, participatory, and ethical development communication interventions.